Perception Enhancements Using Visual Attributes in Sequence Motif Visualization - Kok, Wei Ying; Oon, Yin Bee; Lee, Nung Kion (2014)
Human factor theories are always being neglected especially in the design of biological tools. This problem was found in sequence logo which is used to visualize the conservation characteristics of the biological sequence motifs. Previous studies have found some limitations in the graphical representation which cause biasness and misinterpretation of the results in sequence logo. Therefore, the aim of this study is to investigate on the visual attributes performance in helping viewers to perceive and interpret the information based the preattentive theories and Gestalt principles of perception. A survey was carried out to gather user’s opinion. The results showed some limitations in the use of colour, negative space, size and arrangement of the nucleotides and the lack of information and interactivity in the sequence logo. Therefore, improvements in standardizing the colour, graphical representation of the nucleotides and interactivity of the tool are needed to solve the problems of biasness and misinterpretation of the results in sequence logo visualization.